A felicidade cartesiana - López, Marvin Sebastián Estrada (2018)
The general aim of this dissertation is to offer an analysis of the Cartesian concept of happiness. Two specific topics guide this analysis. The first one is the relation between Cartesian happiness and the theories about this subject of some Ancient Greek philosophers. The second one is the close connection between this idea of happiness and Descartes's particular conception of Philosophy. Descartes introduces a new manner to understand the idea of happiness. However, to state his own definition of happiness, Descartes cannot ignore the Ancient Greek theories and, in fact, he accepts the link between happiness and human nature, one of the typical features of those theories. However, Descartes understands human nature in a different way and feels that the Ancient Greek model needs a revision. Thus, Descartes differs from the traditional Greek theories and affirms that happiness consists in the greatest contentment and the inner satisfaction that the virtuous people enjoy. Cartesian happiness is not the supreme good, which was one of the distinctive features of the Ancient Greek theories. Indeed, that béatitude is the result of the practice of virtue. In other words, Cartesian happiness is the result of the constant process of perfection of human nature. To develop this process correctly, it is necessary to know the real nature of human beings to establish their real abilities and limits. Cartesian happiness is related to human nature and it should be subject of philosophical reflection. The knowledge of real human nature, i.e. soul-body substantial union, is the foundation of this happiness. Only by acknowledging this, we will be able to know our faculties, the highest perfection they can reach and the real motives to esteem ourselves correctly. To attain that natural happiness we only have to use our natural faculties well, i.e. we have to practice virtue. This perfection of our human nature will lead us to acknowledge which is the best use of the natural abilities of our minds and our bodies and that will produce our happiness. Cartesian Philosophy is a virtuous exercise of our natural faculties. That is why this Philosophy occupies a very important place in this process of perfection of human nature. Besides, the truths we discover using Philosophy help us understand our proper relationship with God, with His Creation, and with other people, and thus, they help us lead a better life. The continued practice of virtue allows us to potentiate our faculties to the highest level possible. All of that knowledge leads us to consider the infinite goodness of God and makes us love Him correctly. The Cartesian wise person can perfect her nature as much as possible, can lead the best life her nature permits, and loves God so much that she is able to accept favorably all the events of the world. Therefore, this wise person enjoys the greatest contentment of this life, the modern Cartesian happiness.